Songs of the humpback whale : a novel in five voices - Picoult, Jodi, 1966- (2001)
After a family argument, Jane takes her daughter, Rebecca, and travels across the country to stay with her brother Joley, and Oliver, her oceanographer husband, tries to track her unpredictable path.
"First Pocket Books trade paperback printing October 2001"--T.p. verso.
committed to retain
Keywords: Interpersonal relations -- Fiction; Families -- Fiction